2017
DOI: 10.1103/physrevb.96.035312
|View full text |Cite
|
Sign up to set email alerts
|

Geometric vector potentials from nonadiabatic spin dynamics

Abstract: We propose a theoretical framework that captures the geometric vector potential emerging from the non-adiabatic spin dynamics of itinerant carriers subject to arbitrary magnetic textures. Our approach results in a series of constraints on the geometric potential and the non-adiabatic geometric phase associated with it. These constraints play a decisive role when studying the geometric spin phase gathered by conducting electrons in ring interferometers under the action of in-plane magnetic textures, allowing a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…It has been suggested that this effective phase of geometrical origin could be studied by either interferometric means in ring systems or analyzing resonances in spin or other two-level quantum systems. [33][34][35] Here we show that signatures of a transition sharing some of the features associated to the effective geometric phase may be observed in the anisotropy oscillations considered in this work.…”
Section: Imprints Of Geometric Phase Switchingsupporting
confidence: 61%
“…It has been suggested that this effective phase of geometrical origin could be studied by either interferometric means in ring systems or analyzing resonances in spin or other two-level quantum systems. [33][34][35] Here we show that signatures of a transition sharing some of the features associated to the effective geometric phase may be observed in the anisotropy oscillations considered in this work.…”
Section: Imprints Of Geometric Phase Switchingsupporting
confidence: 61%
“…For the potential application of the model, we note that the spin geometric phase driven by magnetic field textures has been exploited to manipulate electronic quantum states in semiconducting nanostructures [33,34]. Very recently, the role of the nonadiabatic A-A phase of the spin carriers subject to in-plane magnetic textures has also been investigated in relation to the topological transition in electronic spin transport [35,36]. The model proposed in the present manuscript offers a renewed way to address the relevant issue.…”
Section: Discussionmentioning
confidence: 91%
“…However, the spin dynamics is far from being adiabatic in the proximities of the critical line. Recent non-adiabatic treatments [31,32,49] have approached the problem in terms of effective Berry phases linked to the winding parity of spin textures. However, in Sec.…”
Section: Topological Imprints On Two-level Dynamicsmentioning
confidence: 99%